The Effectiveness of the Talking Stick Game in Enhancing Students' Ability to Recall Linguistic Conjugations - Hidayanti, Sri Wahyuni; Hayati, Salma; Safariah, Safariah (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
Linguistic conjugation is an essential part of the science of morphology, it's crucial for understanding Arabic texts. However, students often face difficulties in memorizing linguistic conjugations. Therefore, this study aims to determine the effect of talking stick game on students' ability to remember linguistic conjugation. This research used quantitative approach with quasi experimental method. This study was conducted at MAN 3 Banda Aceh with the subjects amounted to 50 students, consisting of 25 IS class students as the experimental class and 25 IPA class students as the control class. The data were collected through validated tests and analyzed using normality, homogeneity, and t-test analyses. The results showed a significant improvement in the post-test scores of the experimental group (M = 92, SD = 7.77) compared to the control group (M = 64, SD = 14.64). The t-test analysis revealed a significant effect (Sig. 2-tailed = 0.000 0.05). Thus, the implication of this study is that talking stick game as an interactive method can be applied in learning Arabic language especially on linguistic conjugation material or other materials that require strong memory and deep understanding of the material.